(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to reveal the effects of reduced exposure to sunlight and insufficient nutrition due to urbanization and altered cultural life on Vitamin D levels in medical students. Materials and Methods: A hundred (56 female, 44 male) first year medical students were included in our study. A vitamin D screening form, which included 16 questions, was used to obtain data regarding medical students’ genetic, nutrition and cultural life. Results: Out of 100 medical students, 25 hydroxyl vit- D3 levels was below 5 ng/ml in 10%, 5-10 ng/ml in 10%, 10-20 ng/ml in 30%, 20-30 ng/ml in 40% and above 30 ng/ml in 10% medical students. While it has been found out that urbanization causes vitamin D deficiency and insufficiency in both females and males by negatively affecting sunlight exposure and nutrition, females have less sunlight exposure and their vitamin D levels are lesser when compared with males. Conclusions: In conclusion, urbanization decreases exposure to sunlight and changes nutritional habits and forms a basis for vitamin D deficiency. So, this shows that lack of vitamin D, which is a major cause of bone fractures in older ages, is actually mainly seen in younger ages.Keywords: Vitamin D; Sunlight; Nutrition; Cultural Life; Aging.